Perhitungan Biaya Produksi Pada Konveksi Sandang Rakyat Dengan Metode Economic Order Quantity (EOQ) - Akhmad Zakil Umam; Ermayana Megawati (Fakultas Teknik dan Rekayasa, 2023)
The purpose of this study was to determine sales forecasting on production planning at the people's clothing convection. This type of research uses a comparative descriptive method. Descriptive method is a research method that is structured in order to provide a systematic description of scientific information originating from the subject or object of research. comparative method is used to find out how the comparison of the inventory method between the method used by the factory and the Economic Order Quantity method can streamline inventory costs. Based on the results of the analysis of production costs for 2021, it shows that the total production costs incurred by the company are higher at Rp. 29,842,600 while according to the EOQ Rp. 13,706,467 so that with the implementation of EOQ, a savings of Rp. 16,136,133. From the results of the analysis it can be said that with the application of EOQ, the company can obtain inventory cost savings. Thus, from the analysis, it is suspected that sales forecasting is related to production planning using the economic order quantity method at the people's clothing convection Keywords: Compensation, Job Satisfaction, Employee